Thành phần loài và phân bố của mối từ Quảng Bình đến Huế - Minh Duc, Nguyen; Thi Lo, Bui; Thi Ngoc Anh, Do; Thi My, Nguyen; Van Quang, Nguyen; Van Hanh, Trinh (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 1S, 2017)
The result on termite survey from Quang Binh to Thua Thien Hue provinces identified 84 species belonging to 22 genera, 8 subfamilies and 3 families. In comparison with the previous study results, our study newly recorded 27 species and 3 genera in Quang Binh province, two genera in Quang Tri province and six species in Thua Thien Hue province. When we analysed the contribution of termites in different habitats and altitudinal bands, the results showed that the secondary forest habitat has the highest number of species (62 species, accounting for 73.81% of total species number of the studied area), followed by primary forest habitat (41 species, accounting for 48,81%), plantation habitat (34 species, accounting for 40.48%) and resident area with the lowest number of species (23 species, accounting for 27.38%); the number of termite species in the altitudinal band 300-700m is the highest (52 species, accounting for 61.90% of total species number of the studied area), by that in the altitudinal band <300m (41 species, 48.81%), in the altitudinal band 701-1000m (38 species, accounting for 45.23%) and the least is in the altitudinal band > 1000m (21 species, accounting for 25.00%). This is the firstly comprehensive study on composition and distribution of termites in three provinces of Central Vietnam.